The role of AI and digital solutions in ensuring national and global security - Illya Pylypchuk; Nataliia Denysenko (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. Introduction. The world is experiencing a rapid digital transformation that touches nearly every aspect of life, including security. Modern challenges—such as cyberattacks, terrorism, hybrid warfare, and information manipulation—require innovative responses. In this context, artificial intelligence (AI) and digital technologies are increasingly essential for national and global security systems [1, p. 105]; [2, p. 16]. Relevance of Digital Technologies in Security. Digital technologies allow for more efficient monitoring, forecasting, and neutralization of threats. By automating processes and analyzing large volumes of data, authorities, law enforcement, and the military can make faster and more accurate decisions [2, p. 16; 4, p. 16]. This also helps reduce response times and minimize human errors [6, p. 1]. The Role of Artificial Intelligence in Protection Systems. AI can process diverse data sources— from satellite imagery to social media—within unified platforms, identifying patterns and anticipating potential risks [1, p. 105; 6, p. 1]. On a global scale, AI is applied in missile defense, counterterrorism, intelligence analysis, and cyber defense [10, p. 199; 3, p. 133]. AI Applications in Security. Machine-learning algorithms can detect unusual network activity, identify cyberattacks, and block them in real time. This is critical for protecting essential infrastructure such as energy networks, banking systems, and transport hubs [2, p. 17; 6, p. 25]. AI in the Military Sphere. AI is increasingly used to operate unmanned aerial vehicles, automatically recognize targets, and forecast combat scenarios. This reduces risks for personnel and improves operational precision [10, p. 199; 1, p. 105]. Data Analysis Technologies in Law Enforcement. Law enforcement agencies employ facial recognition, voice analysis, and behavioral analytics to monitor suspects, process surveillance footage, and anticipate crime trends [1, p. 45; 6, p. 1].
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: ensuring national and global security; artificial intelligence (AI); Military Sphere